Conceptual Similarities Among Fantasy and Religious Orientations: A Developmental Perspective - Thibodeau, Rachel B. (Journal of cognition and culture, 2018)
Often in conservative religious populations, fantastical thoughts, interests, and beliefs are discouraged because fantastical beliefs are thought to contradict religious doctrine. However, beliefs in invisible, omnipotent entities such as God and Santa Claus likely rely on similar conceptual abilities that might complement rather than contradict religiosity. Therefore, the present study examined how one’s current and retrospective fantasy orientation together are associated with religious orientation. Data from a sample of 150 adults demonstrated that propensity toward fantasy predicted degree of religious orientation in adulthood, even after controlling for an individual’s openness to experience. Specifically, individuals who reported higher fantastical cognitions and behaviors (currently and retrospectively) reported higher religious orientations. These data are counter to cultural concerns that fantastical play and thinking in childhood might undermine or contradict religious doctrine. This finding has important implications for our understanding of how religiosity and fantasy are related conceptually, as well as how cultural practices may impact conceptual development.